Importance of efficacy in achieving coaches` success in football. A perspective from elite athletes and coaches - Duarte, D.; Garganta, J.; Fonseca, A. (International Journal of Sports Science, 2014)
The relevance of the coaches` actions in the development of the sport training process enhances the need to more specifically understand the determinants of their efficacy. With the purpose of studying the efficacy of the football coaches in high-performance football it was used the CESp[2], an adapted version of Coaching Efficacy Scale (CES; Feltz, Chase, Moritz and Sullivan[1]). Participated in this study 244 players and 38 football coaches of the Portuguese Professional Football Leagues. The analysis of results showed there was an agreement between coaches and players on the order of importance of the considered factors, being motivation the most important one. It was also found convergence between the factors indicated as more important by coaches and the behaviours they use to adopt in their practice, as well between the evaluations made by players to the same factors and the correspondent behaviours perceived by them as the more frequently adopted behaviours by their favourite coaches. The conclusions resulting of this study should be considered as an asset in coaches training and consequently, in their performance, contributing to a better understanding of the efficacy factors to be stressed across the training process.